Canadian federal penitentiaries as obesogenic environments: a retrospective cohort study - Johnson, Claire; Chaput, Jean-Philippe; Diasparra, Maikol; Richard, Catherine; Dubois, Lise (Université d'Ottawa | University of Ottawa, 2018)
Background: Very little is known about how incarceration influences a person's weight in Canada. We sought to determine how inmates' weights change during their incarceration in Canadian federal penitentiaries. Methods: We performed a retrospective, longitudinal cohort study to examine weight change in Canadian federal penitentiaries. To participate, inmates had to have been incarcerated for at least 6 months at the time of the study. Current anthropometric data were measured or taken from medical records, then compared with anthropometric data from the beginning of incarceration (mean followup of 5.0 ± 8.3 yr). We examined 3 outcomes: change in weight (kg), change in body mass index (BMI) and rate of weight change (kg/yr) during incarceration. Results: A total of 1420 inmates participated in this study. Almost three-quarters (73.0%, n = 1037)) of participants gained weight during incarceration. Inmates gained a median of 6.2 (95% confidence interval [CI] 5.6–6.9) kg, and BMI increased by 2.0 (95% CI 1.8–2.2). Obesity rates increased by 71%, from 26.6% of participants (n = 378) on admission to 45.4% of participants at follow-up (n = 645). The proportion of inmates with a BMI in the normal range (18.5–24.9) decreased by 52%. Weight gain was found to be associated with older age, region (Ontario v. Atlantic), ethnicity (Aboriginal inmates showed the highest weight gain), longer incarceration, and longer total sentence. However, weight gain was not associated with sex, feeding system or spoken language. Interpretation: The Canadian correctional environment can be considered obesogenic, with most inmates experiencing undesirable and rapid weight gain during their incarceration. Rates of obesity increased dramatically during incarceration, and could put inmates at increased risk of obesity-related health problems.